PROGRAMA DE EXTENSÃO EM GESTÃO DE VAREJO MONITORA INDICE DE CONFIANÇA DE EMPRESÁRIOS VAREGISTAS - Schonhart, Anelize; Sparemberger, Ariosto; Zamberlan, Luciano; Büttenbender, Pedro L.; Hofler, Claudio; Graef, Cleber; Riedner, Karin; Büttenbender, Bruno; Endler, Amanda (Salão do Conhecimento, 2013)
Resumo